FINANCIAL STATEMENT ANALYSIS AND COMPANY PROFILE: ENHANCING MSMES CAPACITY TOWARDS INTERNATIONAL LEVEL: ANALISIS LAPORAN KEUANGAN DAN PROFIL PERUSAHAAN: PENINGKATAN KAPASITAS UMKM MENUJU LEVEL INTERNASIONAL - Nur Rosyidiana, Riska; Miladiah Ervianty, Rizka; Nurul, Mochammad; Nirwana Santy, Afrisa (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economic landscape of a nation. A combination of support from multiple stakeholders can enhance the capacity of MSMEs to effectively fulfill their role. MSMEs have the potential to foster growth not only within local communities but also on a global scale. The ability of the firm's owner to analyze financial statements and build a comprehensive company profile may facilitate the start of internationalization efforts. Objective: The primary objective of this community service initiative is to enhance the knowledge and competencies of business owners in the areas of financial statement analysis and company profile preparation. Method: The training activities are conducted utilizing the pedagogical approach of lectures and interactive focus group discussions. Mentoring activities encompass practical exercises such as the analysis of financial reports and the preparation of business profiles. The data collection process involved the execution of pre-test and post-test, questions and answers, and the completion of activity evaluations by participants. Results: According to the findings, participants' knowledge and skills in assessing financial reports and developing business profiles improved. Conclusion: Financial statement analysis and the creation of company profiles are critical components that cannot be overlooked for MSMEs seeking to compete globally. Financial statement analysis is the fundamental instrument for making informed business decisions, whereas company profiles are visual representations and pictures that help a company develop a strong identity in the global market.